Paediatric pyoderma gangrenosum treated with ustekinumab - Emanuele Savasta; Paola Coppo; Roberta La Selva; Anna Opramolla; Michele Pinon (Wiley, 2024)
Abstract Pyoderma gangrenosum (PG) is a rare reactive noninfectious inflammatory dermatosis. More than 50% of PG patients have an associated systemic disease, which, in most cases, is an inflammatory bowel disease. PG affects more females than males and patients with active colitis. This case report describes a 12‐year‐old girl previously diagnosed with ulcerative colitis (UC) and on infliximab treatment. She came to our attention with a painful leg ulcer during admission for acute respiratory failure and fever. The lesion was classified as PG and a diagnosis of UC pulmonary involvement was made. Infliximab was substitute by ustekinumab and the girl is in remission after 1 year of treatment. To the best of our knowledge, this is the first case in the literature of a UC‐related paediatric PG treated with ustekinumab. Our data suggest that more studies are required as to the efficacy of ustekinumab in paediatric PG settings.